Combined application of biochar and halophyte intercropping enhances cucumber yield and quality by ameliorating soil properties in a continuous cropping system - Shen, Songsong; Xu, Yusheng; Liu, Zhongpeng; Luo, Yating; Wang, Ruifang; Li, Guanlin; Liu, Yujing (Frontiers in Plant Science, 2025)
Biochar amendment and halophyte intercropping are viable strategies for alleviating soil degradation in greenhouse systems, specifically the secondary salinization and autotoxicity induced by continuous cropping. Nevertheless, the potential synergistic effects of combining these practices remain poorly understood. This study investigated their synergistic effects on soil properties, microbial communities, and cucumber performance. A pot experiment was conducted with the following treatments: soil without amendment (CK), biochar (B), Paspalum vaginatum intercropping (S), and biochar combined with Paspalum vaginatum intercropping. The results showed that BS treatment led to the highest increases in soil organic carbon content, pH, total nitrogen content, available phosphorus content, and available potassium content compared to CK (p<0.05). Concurrently, BS significantly reduced available nitrogen, electrical conductivity, Na+, SO42-, and Cl- levels, while total phosphorus remained unaffected. Cucumber yield increased significantly by 11.50% and 27.12% under B and BS treatments, respectively, whereas S showed no significant effect. BS also achieved the highest fruit quality enhancement, followed by B and S. Notably, B and S treatments displayed the highest and lowest K+, Ca2+and Mg2+ accumulation, respectively, whereas the BS treatment led to K+ and Ca2+ concentrations that were significantly lower than those in the B treatment. Soil bacterial diversity was significantly enhanced under BS. The PLS-PM identified the alleviation of soil salinity and acidity, along with improved nutrient availability, as the primary drivers for enhanced crop performance, with soil bacterial diversity playing a secondary yet significant role. These findings suggest that biochar combined with intercropping (BS) effectively mitigates continuous cropping obstacles in greenhouse systems by synergistically improving soil health and microbial ecology.